2010
DOI: 10.1016/j.biopsych.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Cerebral Amyloid Load Is Associated with the Apolipoprotein E ε4 Genotype in Alzheimer's Disease

Abstract: Background-Pittsburgh Compound B ([ 11 C] PiB) is a specific positron emission tomography (PET) marker of cerebral amyloid deposits. Only few data have been published on in vivo longitudinal changes of amyloid load in Alzheimer's disease (AD) patients, with conflicting results. Therefore, little is known about the factors that influence these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 38 publications
(50 reference statements)
7
78
2
5
Order By: Relevance
“…By contrast, the bilateral hippocampus, caudate nucleus, thalamus, amygdala, and parahippocampal gyri had the smallest slope and the lowest AAR. Our findings are well in line with those of Grimmer et al (23), who examined regional progression of Ab in Alzheimer dementia using PET with Pittsburgh compound B (23). As in our study, they found that regions of the frontal lobe followed by those of the parietal lobe showed the highest accumulation rate, whereas the temporal lobe appeared to have the lowest rate across the neocortex.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…By contrast, the bilateral hippocampus, caudate nucleus, thalamus, amygdala, and parahippocampal gyri had the smallest slope and the lowest AAR. Our findings are well in line with those of Grimmer et al (23), who examined regional progression of Ab in Alzheimer dementia using PET with Pittsburgh compound B (23). As in our study, they found that regions of the frontal lobe followed by those of the parietal lobe showed the highest accumulation rate, whereas the temporal lobe appeared to have the lowest rate across the neocortex.…”
Section: Discussionsupporting
confidence: 82%
“…As in our study, they found that regions of the frontal lobe followed by those of the parietal lobe showed the highest accumulation rate, whereas the temporal lobe appeared to have the lowest rate across the neocortex. Further, most of the FARs accumulated Ab faster in the left hemisphere (23). The same order of accumulation rate (frontal .…”
Section: Discussionmentioning
confidence: 63%
“…Among placebo participants with baseline GCA $1.35, carriers showed an increase in 11 C-PiB signal over the course of the study, whereas noncarriers did not. Grimmer et al 17 also found differences by APOE e4 genotype in the progression of the cortical 11 C-PiB-PET signal in participants with AD over a 2-year interval. This finding may suggest that APOE e4 has a sustained influence on Ab Figure 2 Model-estimated effect of bapineuzumab on Ab burden in carriers, noncarriers, pooled studies, and by disease severity accumulation and not just on the timing of its initiation and could also have implications regarding the use of amyloid PET in detecting treatment effects targeting Ab deposition.…”
mentioning
confidence: 92%
“…The association of APOE4 with AD risk was first described in 1993 (6,7), leading to research efforts focused on the effects of the APOE genotype on plaque burden and the structural relationship between apoE and amyloid. IHC analysis demonstrates that plaque deposition is greater with APOE4 compared with APOE3 in AD and nondemented controls (8,9) and that a higher proportion of A␤ within a plaque is associated with apoE4 than with apoE3 (10). Biochemical analysis confirms that the levels of apoE and A␤ are also higher with APOE4 compared with APOE3 in the insoluble extraction fraction from brains of FAD-Tg mice (11).…”
mentioning
confidence: 99%